2013
DOI: 10.1074/jbc.m112.447086
|View full text |Cite|
|
Sign up to set email alerts
|

Phosphorylation Drives an Apoptotic Protein to Activate Antiapoptotic Genes

Abstract: Background: Influenza A matrix 1 protein (M1) associates with nuclear domain 10 (ND10) early in infection. Results: Phosphorylated M1 upon nuclear translocation induces survival genes by inhibiting death domain-associated protein 6 (Daxx) of ND10. Conclusion: M1 in early infection exhibits phosphorylation-dependent antiapoptotic function. Significance: This study uncovers the antiapoptotic role of M1 and identifies a possible therapeutic target to limit virus infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…The phosphorylation of IAV proteins is an important regulatory mechanism that influences viral replication by affecting the nucleocytoplasmic shuttling of both the individual viral proteins themselves and the vRNP complex. Nuclear transport of M1 depends on phosphorylation mediated by protein kinase C (PKC), as PKC inhibition effectively decreases virus replication [ 65 ]. Mutation of the M1 Y132 phosphorylation site in A/WSN/1933 (H1N1) eliminates the interaction between M1 and importin α1, inhibiting M1 nuclear import, and thus having a negative influence on virus replication.…”
Section: Biological Significance Of Nucleocytoplasmic Shuttling Onmentioning
confidence: 99%
“…The phosphorylation of IAV proteins is an important regulatory mechanism that influences viral replication by affecting the nucleocytoplasmic shuttling of both the individual viral proteins themselves and the vRNP complex. Nuclear transport of M1 depends on phosphorylation mediated by protein kinase C (PKC), as PKC inhibition effectively decreases virus replication [ 65 ]. Mutation of the M1 Y132 phosphorylation site in A/WSN/1933 (H1N1) eliminates the interaction between M1 and importin α1, inhibiting M1 nuclear import, and thus having a negative influence on virus replication.…”
Section: Biological Significance Of Nucleocytoplasmic Shuttling Onmentioning
confidence: 99%
“…A cell is thus able to cross the basal membrane and the endothelial wall, to move with the blood flow, to extravasate, and to form a new tumor nest. In this process, a TISC consistently activates the respective gene systems, acquires the property of escaping the attack of the immune cell system [ 40 ] and activates antiapoptotic genes [ 41 44 ]. In addition, TISCs possess other unique qualities, such as the ability to eliminate and neutralize toxins [ 45 49 ], to interact with the cells of the surrounding stroma and to stimulate them to transition to anaerobic respiration (glycolysis), which is known as the Warburg effect [ 50 52 ].…”
Section: Resultsmentioning
confidence: 99%
“…A rabies virus strain with a higher degradation rate of its G protein induced less apoptosis in infected neuronal cells and had a 50% higher pathogenicity index for mice than a variant strain with a lower degradation rate of the G protein [ 46 ]. It is known that the M1 protein of influenza A viruses mediates activation of caspase, which plays essential roles in inducing apoptosis both in viral infected and M1-expressing cells [ 47 ]. Although the transient expression of WZ83 and WZ101 M1 proteins in 293T and Hela cells did not affect the caspase activity (data not shown), our data suggested that the WZ101 M1 protein was more unstable and degraded more rapidly in virus-infected CEF than the WZ83 M1 protein.…”
Section: Discussionmentioning
confidence: 99%